Diagnostic accuracy of fine needle aspiration cytology in neoplasms of solitary nodule in thyroid gland: a retrospective study - V. V., Manoj; Shafi, Shafeer M. (International Surgery Journal, 2021)
Background: Common endocrine disorders like thyroid nodule may represent thyroid neoplasm either benign or malignant and are important to be diagnosed as they may progress and lead to thyroid dysfunction. Fine needle aspiration cytology (FNAC) has emerged as an economic, rapid, effective, simple and accurate strategy for diagnosing neoplastic thyroid nodules. The basic aim of the current investigation was to evaluate the diagnostic accuracy of FNAC in neoplasms of solitary thyroid nodules. Methods: Current investigation was a retrospective diagnostic test evaluation study conducted on 60 patients who underwent total thyroidectomy for solitary nodule for a duration of one year. Routine blood investigation, thyroid function test, FNAC, chest X-ray, indirect laryngoscopy and ultrasound scanning of neck were done for all the patients. Collected data was coded and entered in excel sheets and was statistically analyzed using SPSS. Results: Mean age of the participating patients was 45.51±7.2 years and age range was 24 to 68 years. Female patients were observed to be more than male patients. In majority of the patients duration of nodule was less than or equal to one to three years. Maximum number of patients underwent either total or hemi thyroidectomy. FNAC diagnostic findings revealed patients with NCG, FN, LT, PC and MC. The results of FNAC findings resembled and were supported by HPR findings. Conclusions: Current investigation findings revealed that fine needle aspiration cytology can be considered as potential, accurate, rapid and efficient diagnostic technique for rapid primary investigation of neoplasms of solitary nodules in thyroid gland.